Balance assessment under dual task conditions in patients with total knee arthroplasty: a test-retest reliability and concurrent validity study. - Özcan, Damla; Unver, Bayram; Karatosun, Vasfi (Physiotherapy Theory & Practice, 2025)
Background: Under dual-task (DT), functional mobility and balance testing can detect balance and mobility problems in activities of daily living, especially in situations that cannot be identified under single-task conditions. Objective: Determine the test-retest reliability and concurrent validity of the Four Square Step Test (FSST) under DT conditions for people with total knee arthroplasty (TKA). Method: A total of 30 patients with TKA participated in this research, and patients were tested with the FSST under DT conditions. In addition, concurrent validity of the dual-task FSST was calculated using Timed Up and Go (TUG) under the single-task condition and Hospital for Special Surgery (HSS) Knee Score. Patients performed two FSST trials on the same day under DT conditions. Results: The intraclass correlation coefficients (ICC2,1) two-way random effects model, and minimal detectable changes with 95% confidence intervals (MDC95) values of the FSST under DT conditions were.97 and 3.43, respectively. The Pearson's correlation coefficient of the FSST with the TUG and HSS was.65 and −.40, respectively. Conclusion: The FSST has been found to be a reliable and valid clinical assessment tool for dynamic balance under DT conditions in patients with TKA. For identify balance disorders in daily life at early points, clinicians and researchers can use the FSST under DT conditions in TKA. Clinical Trial registration number: NCT06108466